Redistribution of impurity in ion-doped layers during fast heat treatment of gate dielectric - Anishchik, Victor M.; Harushka, Valiantsina A.; Pilipenka, Uladzimir A.; Ponariadov, Vladimir V.; Saladukha, Vitali A. (Journal of the Belarusian State University. Physics, 2019)
Introduction. The investigation results are shown about influence of the rapid thermal treatment of the gate dielectric for the surface resistance and the location depth of the previously formed ion-doped layers. Experimental methods. On the silicon wafers of the different type of conductivity a gate dielectric was formed with the thickness of 42.5 nm and silicon was doped with the boron and phosphorus ions with the subsequent annealing in the diffusion oven at the temperature of 1150 °С during 90 –270 min in the nitrogen medium. Further, some wafers were subjected to the rapid thermal treatment by means of irradiation of the non-working side with the non-coherent light beam under the natural atmospheric conditions during 7 s at the temperature of 1100 °С. Experimental results and discussion. It was determined, that the given treatment of the gate dielectric, obtained by means of the silicon pyrogenic oxidation, results in reduction of the surface resistance value of the previously formed ion-doped layers by 1–2 % and in increase of the bulk depth of the introduced admixture for 0.05 mm for phosphorus and for 0.02 mm for boron. Conclusion. It was demonstrated, that reduction of the surface resistance value is in correlation with the electric preactivation of the introduced admixture in the rapid thermal treatment, and increase of its bulk depth – with the doubled value of the diffusion ratio, determined by the electric field, occurring under influence of the photon stream.
Keywords: ion-doped layer; fast heat treatment; surface resistance; diffusion factor